People’s perception of the impact of parks on increasing physical activity in the community - Joni Marcio de Farias; Ricardo Teixeira Quinaud (Revista Brasileira de Atividade Física e Saúde)
The present study aimed to analyze the probability of people’s responses about the impact of parks on increasing physical activity in the community. Data was collected with park goers and a total of 427 participants responded to the structured questionnaire with a scale ranging from 1 (not at all) to 10 (totally). Data was analyzed using multilevel ordinal regression analysis considering the variability by gender, civil state, distance from the park, education, age group, living time in the city, time spent by the users in the park and wage. Participants presented similar probabilities of responses. There were found tendencies of lower impact of the parks in older (> 60 years old) and single people as well as in people living further from the parks (> 6 km). The high probabilities of responses were for values 8, 9 and 10. We can conclude people have a perception of the high impact of the parks on increasing physical activity in the community. This study contributes to encourage stakeholders to act in favor of public open spaces and to develop more action in the spaces that already exist.